Marketing Credibility: Chinese newspapers' responses to revenue losses from falling circulation and advertising decline. (4th July 2019) - Wang, Haiyan; Sparks, Colin
Abstract : New communication technologies have had a major impact on the newspaper press in China. They have lost readers and advertisers and have experienced economic difficulties. These have been more severe for the commercially-oriented newspapers than the official party papers. In response to the loss of advertising they have adopted three strategies. The first is internal reorganization. Editorial and business departments have been merged into sections charged with producing both newspaper content and advertising revenue and which have been set explicit revenue targets. The second has been a heavy stress on non-news gathering activities. These include trading favourable coverage for advertising and using the newspaper to develop other non-news businesses. Thirdly, journalists have been encouraged to adapt to business roles and undertake directly commercial tasks. These have included the sale of advertising space and, more indirectly, the exploitation of their professional contacts as leads for their business colleagues. These strategies have eroded, and sometimes completely removed, the firewall between the journalistic and business goals of the newspapers. Journalists are increasingly subordinated to the needs of revenue raising rather than news reporting.